The Influence Of Asset Management On The Financial Performance Of UMKM - Nurul Hikmah Hidayat; Muchriana Muchran (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze the effect of asset management on the financial performance of UMKM. As a pillar of the national economy, UMKM often face challenges in asset management that impact efficiency and profitability. This research adopts a quantitative approach using a survey method involving 30 UMKM in the Makassar City area. Data were collected through questionnaires and analyzed using simple linear regression. The results show that asset management has a significant influence on the financial performance of UMKM. These findings highlight the importance of structured asset management practices in supporting the business growth of UMKM